Outcomes of dogs with recurrent idiopathic pericardial effusion treated with a 3‐port right‐sided thoracoscopic subtotal pericardiectomy. Issue 6 (1st May 2019) - Michelotti, Kurt P.; Youk, Ada; Payne, John T.; Anderson, Jonathan
Abstract: Objective: To describe a 3‐port right‐sided thoracoscopic subtotal pericardiectomy (TSP) to treat dogs with recurrent idiopathic pericardial effusion (RIPE) and report their long‐term survival. Study design: Retrospective case series. Animals: Sixteen client‐owned dogs. Methods: Medical records were searched for dogs with idiopathic pericardial effusion that recurred after 1 or more pericardiocenteses and treated with a 3‐port right‐sided technique (1 subxiphoid camera port and 2 instrument ports on the right side of the dog). Follow‐up consisted of direct examination or communication with referring veterinarians or owners. Results: Thoracoscopic subtotal pericardiectomy was successfully completed in all dogs, with no surgical complications. The median duration of postoperative follow‐up was 191.5 days (range, 5–1345). The median survival time (MST) after surgery was 365 days (range, 5–1345); MST of dogs with a histopathological diagnosis of neoplasia (n = 4) was 76 days, whereas dogs with no evidence of neoplasia had an MST of 367 days (n = 12, P  = .14). Recurrent pleural effusion was the ultimate cause of death or reason for euthanasia in 8 of 16 dogs. Conclusion: The technique described here resulted in similar surgical times and outcomes for dogs undergoing TSP for RIPE compared with previous studies. Neoplasia was identified in 4 of 16 dogs. Clinical significance: Thoracoscopic subtotal pericardiectomy can be readily performed with only 2 instrument ports, both on the same side of the dog, and without 1‐lung ventilation. Recurrent pleural effusion led to the death of half of the dogs in this series.